CsPbBr3-based semiconductor material, preparation method and application thereof

CN115566085BActive Publication Date: 2026-10-13YUNNAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210858668.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-20
Publication Date
2026-10-13
Estimated Expiration
2042-07-20

AI Technical Summary

Technical Problem

一般来说,探测器的响应时间越短,R越高,EQE越大,D*越高,器件的性能就越好,但是材料的限制,现有的光电探测器的性能还有待提升

Benefits of technology

通过将单根CdSeNB转移到单根CsPbBr3MW上,复合成了CsPbBr3MW/CdSe NB杂化光电探测器件,两种材料构建了平行杂化器件;其次,在530 nm处复合材料与纯CsPbBr3MWs都表现出带隙吸收,而复合材料表现出比纯CsPbBr3MWs更强的带隙吸收;此外,复合材料还在710 nm左右表现出带隙吸收,这可以看作是的共吸收。增强的光吸收有利于复合器件的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115566085B_ABST
    Figure CN115566085B_ABST
Patent Text Reader

Abstract

The application discloses a CsPbBr3-based semiconductor material, a preparation method and application thereof, relates to the technical field of semiconductor photoelectric detectors, and comprises the following steps: dropping a prepared CsPbBr3 precursor solution on a Si / SiO2 substrate treated by a plasma instrument, covering a smooth and flat PDMS film, and drying; after drying, the PDMS film is removed, an optical microscope is used for observation, and a substrate on which CsPbBr3 MWs grow well is selected and reserved; 50 muL of CdSe NB dispersion liquid is sucked by a pipette gun, and is dropped on the selected CsPbBr3 MWs substrate, and the solution is completely evaporated; an optical microscope is used for observation, and a sample in which CsPbBr3 MWs and CdSe NB are compounded together is selected; and an evaporation system is used to evaporate Au (80 nm) electrodes on the sample. The CsPbBr3 MW / CdSe NB structure is favorable for improving the photoelectric performance of a device, fully plays the advantages of a large absorption coefficient and high quantum efficiency of a full inorganic perovskite and the excellent performance of a two-dimensional material, and can provide a reference and a reference value for future new high-performance optoelectronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of CsPbBr3-based semiconductor materials in optoelectronic devices, specifically to CsPbBr3-based semiconductor materials, their preparation methods, and their applications. Background Technology

[0002] Compared with traditional semiconductor materials, all-inorganic perovskites have high light absorption coefficients, high sensitivity, and can be prepared by various methods. CsPbBr3 in all-inorganic lead halide perovskite (CsPbX3) is a direct bandgap semiconductor material with significant photoelectric properties such as high light absorption coefficient, high carrier mobility, and long diffusion length.

[0003] All-inorganic CsPbBr3, as a novel semiconductor material, has better stability than organic-inorganic hybrid perovskites, and has therefore attracted widespread attention from researchers. It is one of the candidates for researching novel high-performance optoelectronic devices and has broad applications in fields such as photoelectric detection, solar cells, and light-emitting diodes.

[0004] CdSe nanoribbons (NB) are direct bandgap semiconductor materials, belonging to the II-VI group. They have a bandgap of 1.7 eV and a direct bandgap structure, exhibiting excellent optical properties such as carrier transport. They have been applied in various forms (quantum dots, nanocrystals, nanorods, nanoribbons) in optoelectronic devices, such as electron emitters, spectral analysis, photoconductors, semiconductors, and photosensitive elements.

[0005] As a crucial component of information transmission, photodetectors convert light signals into electrical signals through the photoelectric effect, enabling information transmission. Currently, they have important applications in biosensing, image sensing, missile early warning, and optical communication. Generally, the shorter the detector's response time, the higher the R-value, the larger the EQE, and the higher the D*, the better the device's performance. However, due to material limitations, the performance of existing photodetectors still needs improvement.

[0006] Therefore, its combination with a high-photon-absorption all-inorganic perovskite layer may pave the way for novel high-performance optoelectronic devices. Summary of the Invention

[0007] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides CsPbBr3-based semiconductor materials, preparation methods, and applications. Large-size, high-quality CsPbBr3MWs were prepared using an in-plane self-assembly method. Subsequently, CdSeNB two-dimensional materials were grown using CVD. A single CdSeNB was then transferred onto a single CsPbBr3MW to form a CsPbBr3MW / CdSeNB hybrid device. A hybrid device is constructed by combining CdSe NB and CsPbBr3MWs, which combines the high carrier transport characteristics of CdSe NB and the high photon absorption characteristics of CsPbBr3MWs. This fully leverages the advantages of both in photodetector devices, improves the photoelectric performance of the device, and solves the problems in the background technology.

[0008] (II) Technical Solution In this application, CsPbBr3 microwires (MWs) were synthesized and their photoelectric properties were systematically studied. Next, CdSeNBs were grown using chemical vapor deposition (CVD), and a CsPbBr3MW / CdSeNB hybrid optoelectronic device was constructed. Analysis of the photoelectric performance of the hybrid device showed that, compared to a single CsPbBr3 device, the hybrid device exhibited a wider spectral response (from ultraviolet to visible light) and a significant improvement in photoelectric performance. Finally, a reasonable explanation was provided for the microscopic physical mechanism underlying the improved photoelectric performance of the hybrid device.

[0009] This invention is achieved through the following technical solution: This invention provides a method for preparing CsPbBr3MWs based on in-plane self-assembly, comprising the following steps: A smooth and flat PDMS film is prepared on a smooth and flat Si substrate with a photoresist-free microstructure; Equimolar amounts of PbBr2 and CsBr powders are weighed using an electronic balance and dissolved in a container containing 1 ml of dimethyl sulfoxide (DMSO) solution, and then tightly sealed; the container is placed in an oil bath and stirred at 65°C for 6 hours, then removed, cooled to room temperature, and filtered through a 0.45 μm polytetrafluoroethylene needle filter; 10 μL of CsPbBr3 solution is pipetted onto the prepared Si / SiO2 substrate, and a PDMS film cut to the size of a silicon wafer is pressed onto it and dried overnight on a 45°C hot plate; after removing the covering substrate, the CsPbBr3MWs material is obtained.

[0010] This invention also provides a method for fabricating a CsPbBr3MWs material device, comprising the following steps: dropping a CsPbBr3MWs precursor solution onto a Si / SiO2 substrate, covering it with a smooth and flat PDMS film, and then placing it on a 50 ℃ drying stage overnight; removing the PDMS film, and fixing the Si / SiO2 substrate with good morphology onto a mask with a diameter of 10 μm wound around it under an optical microscope; placing the Si / SiO2 substrate fixed by the mask into an electron beam evaporation system to deposit an 80 nm gold electrode; after the deposition is completed and cooled, removing the sample; finally, selecting samples whose two ends are in contact with Au electrodes respectively, which are the CsPbBr3MWs devices.

[0011] The present invention also provides an optoelectronic device based on CsPbBr3MWs material, comprising a CsPbBr3MWs device.

[0012] This invention also provides a method for preparing CdSeNBs based on CVD growth, comprising the following steps: Si / SiO2 substrates cut into 1.0×2.0cm pieces are ultrasonically cleaned for 10 min each in acetone, ethanol, and deionized water, then dried with nitrogen gas. A 10nm thick Au film is then sputtered onto the substrate. An appropriate amount of CdSe powder is placed in a ceramic boat and compacted to prevent it from being blown away by the gas. The ceramic boat is placed in the middle of a quartz tube, and the silicon substrate is placed approximately 6cm downstream of the ceramic boat for depositing two-dimensional materials. The quartz tube is placed in a tube furnace, its position determined, and the flange closed. Ar / H2 gas (H2 content 5%) is then introduced to clean the tube furnace. After cleaning, a vacuum is drawn, and the flow rate of the mixed gas is controlled at 15 sccm. The temperature is increased at a rate of 10℃ / min from room temperature to 300℃, held at this temperature for 10 min, then increased to 820℃ and held at this temperature for approximately 120 min. The substrate is cooled to room temperature and then removed, completing the growth of CdSeNBs.

[0013] This invention also provides a method for fabricating a CdSeNB material device, comprising the following steps: Dispersing the sample: Observing the surface morphology of the deposited CdSeNBs using a scanning electron microscope to identify regions of CdSeNBs that meet the following conditions (high density, uniform growth, and thin thickness); gently scraping the identified region into a centrifuge tube containing anhydrous ethanol using tweezers, and gently shaking to ensure uniform dispersion of CdSeNBs in the ethanol solution; using a pipette to drop 50 μL of the dispersion onto a clean Si / SiO2 substrate, allowing the anhydrous ethanol to completely evaporate at room temperature, and then observing the density of the CdSeNBs. The above steps can be repeated multiple times to increase the density of the CdSeNBs; Fabricating the device: Selecting CdSeNBs with high density and uniform distribution, using a mask template, winding a 10 μm diameter tungsten wire around it, fixing it, and placing it on the sample stage of the evaporation chamber and fixing it; depositing 80 nm of gold; finally, after the program completes and the instrument is turned off, the CdSeNB device fabrication is complete.

[0014] This invention also provides a method for fabricating a hybrid device based on CsPbBr3MWs and CdSeNB, comprising the following steps: dropping a prepared CsPbBr3 precursor solution onto a Si / SiO2 substrate treated with a plasma analyzer, covering it with a smooth and flat PDMS film, and drying it; after drying, removing the PDMS film, observing it with an optical microscope, and selecting substrates with better CsPbBr3MWs growth for later use; using a pipette to take 50 μL of CdSeNB dispersion and dropping it onto the selected CsPbBr3MWs substrate, waiting for the solution to completely evaporate; observing and selecting samples where CsPbBr3MWs and CdSeNB are combined using an optical microscope; evaporating an Au (80 nm) electrode onto it using an evaporation system; the CsPbBr3MWs / CdSeNB hybrid optoelectronic device is thus fabricated.

[0015] The present invention also provides a CsPbBr3-based semiconductor material comprising a CsPbBr3MW / CdSeNB hybrid device.

[0016] The present invention also provides the use of CsPbBr3MW / CdSe NB material in photodetectors, solar cells or light-emitting diodes.

[0017] The present invention also provides the use of CsPbBr3MW / CdSe NB material in improving the performance of optoelectronic devices.

[0018] (III) Beneficial Effects This invention provides a method that has the following beneficial effects: By transferring a single CdSeNB strand to a single CsPbBr3MW strand, a CsPbBr3MW / CdSeNB hybrid photodetector was synthesized, forming a parallel hybrid device. Secondly, both the composite material and the pure CsPbBr3MWs exhibited bandgap absorption at 530 nm, with the composite material showing stronger bandgap absorption than the pure CsPbBr3MWs. Furthermore, the composite material also exhibited bandgap absorption around 710 nm, which can be considered as co-absorption. This enhanced light absorption is beneficial for the application of the composite device.

[0019] The CsPbBr3MW / CdSeNB composite device exhibits a large photoresponse in the 300-740 nm range, with two photoresponse peaks at 530 nm and 710 nm. Therefore, the photoelectric performance of the CsPbBr3MW / CdSeNB composite device was investigated using 530 nm and 710 nm as representative values.

[0020] The CsPbBr3MW / CdSe NB structure is beneficial for improving the optoelectronic performance of devices because the combination of a fully inorganic perovskite layer with high photon absorption and a carrier transport layer opens up more possibilities for building high-performance detectors. It combines high light absorption and high conductivity, giving full play to the advantages of the large absorption coefficient and high quantum efficiency of fully inorganic perovskites, as well as the excellent performance of two-dimensional materials, and may provide reference and reference value for future novel high-performance optoelectronic devices. Attached Figure Description

[0021] Figure 1 This is the (a) SEM image of CsPbBr3MWs in this invention (Inset: SEM image of a single CsPbBr3MWs). (b) HRTEM (inset SAED plot); (cd) 2D and 3D DAF plots of CsPbBr3MWs Figure 2 For the present invention, the following are the following images of CsPbBr3MW: (a) EDS image; (b) SEM image; (cf) elemental mapping image. Figure 3 The XRD pattern of CsPbBr3MWs in this invention. Figure 4 The XPS spectra of CsPbBr3MWs in this invention are: (a) full spectrum; (b) Cs3d; (c) Pb4f; (d) Br3d. Figure 5 In this invention, the UV-vis spectrum (a) of CsPbBr3MWs (b) (αhν) is shown. 2 The relationship between photon energy Figure 6 The PL spectrum of CsPbBr3MWs in this invention. Figure 7 The following are the IV curves of the CsPbBr3MWs photodetector in this invention: (a) SEM image of the device; (b) IV curve; (c) logarithmic plot. Figure 8 The spectral response diagram of the CsPbBr3MWs photodetector in this invention is shown. Figure 9 The following are the photoelectric properties curves of CsPbBr3MWs under 530nm irradiation in this invention: (a) IV curves at different powers; (b) IV curves after logarithmic processing of (a); (c) Relationship between photocurrent and optical power density; (d) Relationship between different optical power densities and spectral response and quantum efficiency. Figure 10 In this invention, the bias voltage is 3V and the power density is 1.60μW / cm². 2IT plots of a CsPbBr3MW device under 530nm illumination: (a) periodic IT curve; (b) IT response of a single switch. Figure 11 This is a flowchart illustrating the fabrication of the CsPbBr3MWs / CdSeNB device in this invention. Figure 12 SEM images of CdSeNBs in this invention: (a) low magnification; (b) high magnification; (c) tip of a single CdSeNB; (d) cross-section. Figure 13 The XRD pattern of CdSeNBs in this invention. Figure 14 The images shown are (a) TEM image, (b) HRTEM image, and (c) SAED image of a single CdSeNB in ​​this invention. Figure 15 For the purposes of this invention, the XPS spectra of CdSeNBs are as follows: (a) the total XPS spectrum of CdSeNBs; (b) the XPS spectra of Se and (c) Cd elements. Figure 16 In this invention, (a) the UV-vis diagram corresponding to CdSeNBs; (b) (αhν) 2 Relationship diagram with hν Figure 17 For the Raman spectrum of CdSeNBs in this invention Figure 18 (a) SEM image of the CsPbBr3MW / CdSeNB device in this invention; (b) schematic diagram. Figure 19 The UV-vis images of pure CsPbBr3MWs and CsPbBr3MWs / CdSeNB hybrid devices in this invention are shown below. Figure 20 (a) Device diagram of a single CdSeNB in ​​this invention; (b) Logarithmic IV curve. Figure 21 In this invention, the CsPbBr3MW / CdSeNB device operates at a bias voltage of 3V and a wavelength of 530nm (optical power density of 1.6mW / cm²). 2) Performance diagrams under incident light: (a) IV curve; (b) IV curve after logarithmic processing of (a). Figure 22 The image shows the spectral response of the CsPbBr3MWs / CdSeNB device in this invention. Figure 23In this invention, the CsPbBr3MWs / CdSeNB device under 3V bias and illumination with monochromatic light of different powers (530nm) is shown in (a) IV diagram; (b) logarithmic diagram corresponding to (a); (c) relationship between current and optical power density; and (d) relationship between optical power density and R and EQE, respectively. Figure 24 In this invention, the following graphs are used to illustrate the relationship between photocurrent and optical power density of the CsPbBr3MWs / CdSeNB device under the following conditions: (a) IV curves; (b) IV curves after logarithmic processing of (a); (c) the relationship between photocurrent and optical power density after fitting; and (d) the relationship between different optical power densities and R and EQE. Figure 25 The graphs showing the relationship between detectivity and optical power density of the CsPbBr3MW / CdSeNB device in this invention are shown in (a) with incident light at 530 nm and (b) with incident light at 710 nm. Figure 26 For the present invention, the CsPbBr3MW / CdSeNB device under 530nm illumination (bias voltages of 1, 3, 5, and 7V) presents (a) a periodic switching IT diagram and (b) a single-cycle switching IT diagram. Figure 27 This is a flowchart illustrating the fabrication process of the CsPbBr3MWs photodetector in this invention. Detailed Implementation

[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1: Preparation and Characterization of CsPbBr3MWs Experimental materials The materials used to fabricate CsPbBr3MWs devices are shown in Table 1: Table 1 Experimental materials for CsPbBr3MWs

[0024] The experimental apparatus used to prepare CsPbBr3-based devices is shown in the table below: Table 2. Experimental instruments and characterization equipment required for fabricating CsPbBr3MWs devices

[0025] Example 2

[0026] refer to Figures 1 to 27 The preparation method of CsPbBr3MWs based on in-plane self-assembly described in this embodiment includes the following steps: Step S21: Based on the smooth and flat Si substrate with a photoresist-free microstructure, a smooth and flat PDMS film is fabricated. Step S22: Weigh equimolar amounts of PbBr2 and CsBr powders using an electronic balance, dissolve them in a container containing 1 ml of dimethyl sulfoxide (DMSO) solution, and seal tightly. Step S23: Place the container in an oil bath, stir at 65°C for 6 hours, remove and cool to room temperature, then filter with a 0.45μm polytetrafluoroethylene needle filter. Step S24: Use a pipette to draw 10 μL of CsPbBr3 solution and drop it onto the treated Si / SiO2 substrate. Then cut a PDMS film the size of the silicon wafer and press it onto the substrate. Place it on a 45°C hot plate to dry overnight. Step S25: After removing the covering substrate, CsPbBr3MWs material is obtained.

[0027] Characterization of CsPbBr3MWs Figure 1 (a) shows the CsPbBr3MWs synthesized using an in-plane self-assembly method, which, in short, is prepared with the assistance of a PDMS film with a smooth and flat surface and no microstructure. The inset shows a SEM image of a single CsPbBr3MW. The results show that the grown microwires are disordered but relatively uniformly distributed, with smooth surfaces, sharp edges, and lengths ranging from tens to hundreds of micrometers, with widths around tens of micrometers.

[0028] To further investigate the microstructure of CsPbBr3MWs, HRTEM and SAED images of CsPbBr3MWs were characterized. like Figure 1 As shown in (b), the calculated spacing between adjacent lattice fringes is 0.58 nm, corresponding to the (100) crystal plane; the clear and regular diffraction spots in the SAED pattern in the inset further demonstrate that the prepared CsPbBr3MWs has good crystal quality and is a single crystal.

[0029] like Figure 1 As shown in (cd), AFM testing further confirmed the acquisition of CsPbBr3MWs with an ultra-smooth surface and a thickness of approximately 2.9 μm.

[0030] Figure 2 (a) EDS analysis of CsPbBr3MWs. The atomic ratio of Cs, Pb and Br is close to 1:1:3, which is in good agreement with the stoichiometric ratio of CsPbBr3. Figure 2(bf) shows the SEM image of a single CsPbBr3MAs and the elemental mapping of Cs, Pb, and Br. The CsPbBr3MW has a smooth surface, clean edges, and uniform elemental distribution, indicating that the CsPbBr3 crystal has good crystallinity and few defects, which is beneficial to improving the stability of the micron-wire.

[0031] XRD pattern of CsPbBr3MWs prepared on a Si substrate. like Figure 3 As shown, there are two distinct characteristic peaks at 2θ=15.2° and 2θ=30.68°, which are sharp and narrow, indicating that the prepared microwires have good crystallinity.

[0032] To analyze the bond states and chemical composition of CsPbBr3MWs, XPS energy dispersive spectroscopy was further performed, such as... Figure 4 As shown in (ad).

[0033] Figure 4 (a) is the total MWs spectrum of CsPbBr3, and the detected elements are Cs, Pb, Br, C, and O; from Figure 4 (bc) can be used to obtain Cs 3d 5 / 2 and Cs 3d 3 / 2 The corresponding binding energies are 723.94 eV and 737.92 eV, respectively; Pb⁴f 7 / 2 and Pb 4 f 5 / 2 The corresponding binding energies are 138.18 and 142.98 eV, respectively; Br 3d 5 / 2 and Br 3d 3 / 2 The corresponding binding energies are 67.99 eV and 68.98 eV, respectively, which are consistent with the results of CsPbBr3 reported in previous literature. In addition, the SEM, XRD and XPS analysis results can prove that the prepared CsPbBr3MWs have high crystal quality.

[0034] The optical properties of CsPbBr3MWs were tested using UV-vis absorption spectroscopy, such as... Figure 5 As shown in (a), it is clear that there is strong absorption in the range of 300–550 nm. Figure 5 (b) corresponds to (ahv) in the UV-vis map. 2 Using the hv diagram and the Tauc relationship formula 2.1, the optical band gap value E of CsPbBr3MWs can be calculated. g =2.32 eV, such as Figure 5 As shown in (b).

[0035] Figure 6This is the PL spectrum of CsPbBr3 MWs. A distinct emission peak can be seen at 520 nm, which is consistent with... Figure 2 The optical band gap value of CsPbBr3MWs calculated using the Tauc relation formula is consistent with the measured ultraviolet absorption spectrum.

[0036] Photoelectric properties of CsPbBr3MWs Figure 7 (a) is a SEM image of a single CsPbBr3 MW device. Figure 7 (b) A single CsPbBr3 MW device under a bias voltage of 3V and an incident light of 530 nm (optical power density of 1.6 mW / cm²). 2 The image shows the IV curves measured under both illumination and darkness conditions. Under illumination, the irradiated light excited many photogenerated carriers, and the photocurrent significantly increased to 1.37 × 10⁻⁶. -8 A, dark current approximately 1.24 × 10⁻⁶ -11 A. The switching ratio is 1.11 × 10⁻⁶. 3 .

[0037] Figure 7 (c) is Figure 7 (b) The logarithmic IV curve shows that the dark current has a zero-point drift, which may be due to the drift motion of charge carriers.

[0038] Photoconductive properties of CsPbBr3MWs photodetectors To evaluate the selectivity of the studied CsPbBr3 photodetector to incident light, the spectral response of the device in the 300–600 nm range was measured, such as… Figure 8 As shown, similar to the spectral response of CsPbBr3MWs, the device also exhibits a significant spectral response in the 300–550 nm wavelength range, with a sharp decrease in light response around 530 nm. This is consistent with the UV-vis absorption spectrum previously measured for CsPbBr3MWs. The device also reaches its maximum light response at 530 nm, indicating good wavelength selectivity. Therefore, this paper will next investigate the photoelectric performance of a single CsPbBr3MW device under 530 nm monochromatic light illumination.

[0039] The photoelectric performance of a single CsPbBr3MW photodetector was measured under different power conditions with a bias voltage of 3 V and 530 nm monochromatic light illumination.

[0040] Figure 9 (a) is the IV curve of the optoelectronic device. Experiments show that the photocurrent increases significantly with increasing optical power.

[0041] Figure 9(b) is Figure 9 (a) The processed logarithmic curve, which shows that at an optical power of 1.6 mW / cm², the curve is suitable for the following conditions. 2 Under monochromatic light illumination, the photocurrent reaches its maximum value.

[0042] Figure 9 (c) shows the fitting graph of different optical power densities and photocurrents for a single CsPbBr3MW photodetector. The θ value of the fitted single CsPbBr3MW device is 0.94.

[0043] Figure 9 (d) is a graph showing the relationship between different optical power densities and spectral responsivity and quantum efficiency.

[0044] The output signal capability of the CsPbBr3MW device is reflected by its spectral responsivity. Under monochromatic light (530 nm) illumination, with an optical power density set to 0.01 mW / cm², the signal is measured. 2 Under these conditions, the peak responsivity is 2.7 A / W. EQE refers to the ratio of the number of electrons generated to the number of photons in the incident light when incident light irradiates the device surface. The quantum efficiency reaches a maximum of 632% under monochromatic light irradiation at 530 nm. Both quantum efficiency and photoresponsivity gradually decrease with increasing optical power density.

[0045] CsPbBr3MWs optoelectronic device time-current (IT) characteristics Figure 10 The results showed that at a bias voltage of 3 V and a wavelength of 530 nm (power density of 1.6 mW / cm²), the image was obtained. 2) Current-time (IT) characteristic curves of the photodetector under incident light. The dynamic light response of the perovskite photodetector is stable, indicating that the device has very stable photosensitivity. Figure 10 (b) shows the voltage rise and decay edges of the resistor tested using an oscilloscope, with rise times of 10 ms and decay times of 8.5 ms.

[0046] In the above embodiments, highly ordered and highly crystalline large-size CsPbBr3MAs were prepared using a PDMS template-assisted method; subsequently, CsPbBr3MWs were synthesized using an in-plane self-assembly method. Finally, Au electrodes were deposited using an electron beam evaporation system to fabricate optoelectronic devices.

[0047] Surface morphology and microstructure analysis of the CsPbBr3 group were performed using SEM and TEM, indicating that the prepared CsPbBr3 group has good crystallinity. Crystal structure, phase composition, bond state, chemical composition, and elemental analysis of the CsPbBr3 group were further performed using XRD, XPS, and EDS, confirming the preparation of high-crystallinity CsPbBr3MAs and CsPbBr3MWs.

[0048] Optical properties were analyzed using PL and UV-vis, revealing significant optical selectivity in the CsPbBr3-based array. Comparative studies of the photoelectric properties of the two CsPbBr3-based arrays showed that the CsPbBr3MAs devices, composed of multiple micrometer-scale lines, outperformed single-line CsPbBr3MWs devices, even though the micrometer-scale line array was biased at 2 V, while the single-line CsPbBr3MWs device was biased at 3 V.

[0049] However, since the CdSe dispersion is randomly dispersed on the prepared CsPbBr3-based sample, it is often a single CdSe NB combined with CsPbBr3 MWs. Therefore, the combination of CdSe NBs and CsPbBr3 MWs will not be considered in the following study. Instead, we will only consider combining a single CsPbBr3 MW with a single CdSe NB and study its photoelectric properties.

[0050] The study of the photoelectric properties of CsPbBr3MWs revealed that the spectral response range of CsPbBr3MWs is between 300 and 550 nm, with 530 nm being the peak response point.

[0051] Next, the device performance under 440 nm and 530 nm monochromatic light irradiation was compared, further demonstrating that CsPbBr3MWs is more sensitive to 530 nm monochromatic light. The IT curves illustrate the significant stability of CsPbBr3MWs.

[0052] Example 3: Fabrication, characterization, and photoelectric performance study of CsPbBr3MW / CdSe NB device Experimental materials The chemical reagents and materials used to grow CdSe NBs and prepare CsPbBr3MW / CdSe NB composite devices are shown in Table 3.

[0053] Table 3 Chemicals required for the preparation of CsPbBr3MW / CdSeNB

[0054] The instruments required for the experiment are shown in Table 4: Table 4. Instruments and equipment used to prepare CsPbBr3MW / CdSe NB devices

[0055] Example 4: Growth of CdSe NB Please see Figure 1-27 The method for preparing CdSeNB based on CVD growth described in this embodiment.

[0056] First, silicon substrates cut into 1.0×2.0cm pieces were ultrasonically cleaned in acetone, ethanol, and deionized water for 10 minutes, respectively, and then dried with nitrogen. Next, a 10nm thick gold film was sputtered onto the substrate. Then, an appropriate amount of CdSe powder was placed into a ceramic boat and compacted to prevent it from being blown away by the gas. Finally, the ceramic boat was placed in the middle of the quartz tube, and the silicon substrate was placed about 6cm downstream of the ceramic boat for the deposition of two-dimensional materials.

[0057] CdSeNBs growth: First, the quartz tube is placed into the tube furnace and the flange is closed. Then, Ar / H2 gas (H2 content is 5%) is introduced to clean the tube furnace. After cleaning, a vacuum is drawn and the flow rate of the mixed gas is controlled at 15 sccm.

[0058] Set the program to increase the temperature at a rate of 10°C / min from room temperature to 300°C, then hold this temperature for 10 minutes, followed by increasing the temperature to 820°C and holding this temperature for approximately 120 minutes. Finally, allow the program to finish and cool to room temperature before removing it from the refrigerator.

[0059] Example 5: Fabrication of CdSe NB Device Please see Figure 1-27 This embodiment describes a device fabrication method using CdSe NB material. Sample Dispersion: The surface morphology of the deposited CdSeNBs was observed using scanning electron microscopy to identify regions of CdSeNBs that met the specified conditions (high density, uniform growth, and thin thickness). Using tweezers, the identified region was gently scraped into a centrifuge tube containing anhydrous ethanol, and gently shaken to ensure uniform dispersion of the CdSeNBs in the ethanol solution. Then, 50 μL of the dispersion was pipetted onto a clean Si / SiO2 substrate. After the anhydrous ethanol had completely evaporated at room temperature, the density of the CdSeNBs was observed. This process can be repeated multiple times to increase the density of the CdSeNBs.

[0060] Device fabrication: Select CdSeNBs with high density and uniform distribution, fix them with a mask (with tungsten wires with a diameter of 10 μm), place them on the sample stage of the evaporation chamber and fix them, then deposit 80 nm of gold by evaporation, and finally wait for the program to complete and turn off the instrument to complete the device fabrication.

[0061] Example 6: Fabrication of CsPbBr3MW / CdSeNB Device Please see Figure 1-27 The device fabrication method of CdSeNB material described in this embodiment includes the following steps: The specific process for fabricating CsPbBr3MW / CdSeNB devices is as follows: Figure 11 As shown: First, the prepared CsPbBr3 precursor solution was dropped onto a Si / SiO2 substrate that had been treated with a plasma analyzer, and a smooth and flat PDMS film was placed on top. After drying, the PDMS film was removed, and the substrate with better CsPbBr3MWs growth was selected for later use by observation with an optical microscope. Next, use a pipette to draw 50 μL of CdSeNB dispersion and drop it onto the selected CsPbBr3MWs substrate, and wait for the solution to evaporate completely; Then, the CsPbBr3MWs and CdSeNB composite samples were observed and selected using an optical microscope. Subsequently, Au (80 nm) electrodes were deposited on them using an evaporation system to prepare CsPbBr3MWs / CdSeNB hybrid optoelectronic devices.

[0062] Characterization of CdSeNB The surface morphology and growth mechanism of CVD-grown CdSeNBs were observed and analyzed using scanning electron microscopy, such as... Figure 12 (ad). Figure 12 (a) shows that CdSeNBs have a high density, relatively uniform width, and a length of several hundred micrometers. Therefore, they can be used to fabricate devices using photomasks. Figure 12 (b) is Figure 12 (a) The corresponding high-magnification SEM image shows that the surface of CdSeNBs is relatively smooth, with sharp edges and a width in the micrometer range. From Figure 12 (c) As can be seen, there is a spherical structure at the top of the CdSeNBs. This is because the growth process of CdSeNBs requires gold as a catalyst to induce its growth. Therefore, a 10nm thick gold film was sputtered on the substrate. During the growth process, the gold film shrinks and becomes granular due to the increase in temperature. Figure 12 (d) The cross-sectional view of CdSeNB shows that the thickness of CdSeNBs is less than 100 nm, which is a condition for composite nanomaterials.

[0063] XRD data from CdSeNBs phase analysis like Figure 13 As shown, the 2θ peaks in the figure are located at 24.02°, 25.68°, 27.24°, 35.30°, 42.10°, 46.08°, 49.84° and 55.98°, respectively, and can be identified as diffractions of the (100), (002), (101), (102), (110), (103), (112) and (202) crystal planes, corresponding to the standard card JCPDS NO:08-0459.

[0064] Because gold is used as a catalyst during the growth of CdSeNBs, diffraction peaks of gold were detected. The corresponding XRD standard card is JCPDS NO: 04-0784. The 2θ peaks are located at 348.18° and 44.39°, respectively, and can be identified as (111) and (200) crystal planes. The diffraction peaks in the figure are clear and free of impurities, indicating that the prepared CdSeNBs are relatively pure and have good crystallinity.

[0065] The microstructure of CdSeNBs was observed and analyzed using transmission electron microscopy, such as... Figure 14 As shown in (ac).

[0066] Figure 14 (a) is a TEM image of a single CdSeNB strand. It can be seen that the CdSeNB surface is smooth and the edges are sharp and regular. From... Figure 14 (a) Corresponding HRTEM Figure 14 (b) It can be seen that the lattice stripes are relatively clear, and the spacing between adjacent crystal planes is 0.33 nm, corresponding to the (101) crystal plane, which is consistent with the XRD pattern.

[0067] Select an electron diffraction (SAED) pattern, such as... Figure 14 As shown in (c), the clear and regular diffraction spots in the SAED pattern further demonstrate that the grown CdSeNB has good crystal quality and is a single crystal.

[0068] X-ray photoelectron (XPS) full spectrum of CdSeNBs like Figure 15 As shown, the C peak with a binding energy of 284.8 eV was used as the calibration peak for calibration. Figure 15 The elements detected in (a) are Se, C, Cd and O peaks in sequence. Figure 15 (b) is Cd3d 5 / 2 and Cd3d 3 / 2 The XPS spectra corresponding to the peak regions are 405.28 eV and 411.99 eV, respectively, and the distance between the two peaks is calculated to be 6.71 eV. Figure 15 (c) shows the XPS spectrum corresponding to the Se3d region, with the positions of the two main peaks at 53.74 and 54.6 eV, which is consistent with previous reports.

[0069] Figure 16 These are the UV-vis and (ahv) plots of CdSeNBs. 2 A diagram showing the relationship between hv and hv.

[0070] Figure 16 (a) shows that the absorption peak of CdSeNBs remains stable in the range of 500 to about 740 nm, drops rapidly after about 710 nm and then shows a significant absorption peak.

[0071] Figure 16 (b) is Figure 16 (a) The band gap of CdSeNBs is calculated to be E using the formula and linear extrapolation. g =1.74 eV. The surface state, electronic and band structure of CdSe semiconductor material were analyzed by PL characterization, and PL tests were performed using a 532 nm excitation source.

[0072] like Figure 17 As shown in the figure, a significant emission peak was observed at 714 nm, with no other impurity peaks, demonstrating that high-crystallinity, high-purity, and pure CdSeNBs were obtained via CVD. This is consistent with the calculated band gap (1.74 eV).

[0073] Characterization of CsPbBr3MW / CdSeNB like Figure 18 As shown, this experiment synthesized a broadband and high-performance CsPbBr3MW / CdSeNB hybrid optoelectronic device by combining a single CdSeNB with a single CsPbBr3MW, aiming to significantly improve the optoelectronic performance and response range of the CsPbBr3MWs. The effective area of ​​the device was calculated to be 8 × 10⁻⁶. -6 cm 2 .

[0074] To understand the mechanism of enhanced photoelectric response and broadened response after CsPbBr3MWs is combined with CdSeNB, the optical properties of pure CsPbBr3MWs and CsPbBr3MW / CdSeNB composite materials were characterized.

[0075] Figure 19 The UV-vis absorption spectra of CsPbBr3MWs and CsPbBr3MWs-CdSeNB composites in the 300-800 nm range are shown.

[0076] Clearly, compared to pure CsPbBr3MWs, the composite structure exhibits stronger absorption in the ultraviolet to visible light region, indicating its higher light-harvesting ability. The two absorption onset values ​​of the CdSeNB / CsPbBr3MW composite structure are located at 530 nm and 710 nm, respectively.

[0077] In contrast, the hybrid structure exhibits enhanced absorption spectra not only in the 300-550 nm range but also at 530 nm and 740 nm, which can be attributed to the co-absorption of CdSeNB and CsPbBr3MWs. This enhanced light absorption is beneficial for improving the performance of the CsPbBr3MW / CdSeNB hybrid device.

[0078] CsPbBr3MW / CdSeNB photoelectric properties Electrical performance of CdSeNB photodetectors Single CdSe NB photodetector device, such as Figure 20 As shown in (a), the effective area of ​​the optoelectronic device is 2.2 × 10⁻⁶. -6 cm 2 At a bias voltage of 1 V and a wavelength of 710 nm (optical power density of 1.6 mW / cm²), 2) The IV curves after logarithmic treatment under laser irradiation and darkness conditions are as follows: Figure 20 As shown in (b). The results show that the dark current of CdSe NBs in the absence of light is 4.05 × 10⁻⁶. -11 A, while the photocurrent under light irradiation is 8.32 × 10⁻⁶. -8 A is much larger than the current under dark conditions, so the switching ratio is 2.05 × 10⁻⁶. 3 Secondly, the logarithmic curve exhibits high symmetry, indicating good contact between the CdSe NB and the metal electrode. This demonstrates that CdSe NBs have significant light sensitivity. Furthermore, CdSe NBs possess carrier transport properties. Therefore, combining the all-inorganic perovskite layer with excellent high photon absorption characteristics and the carrier transport layer will fully leverage the advantages of both. Thus, the preferred approach is to composite two-dimensional CdSe NBs with CsPbBr3MWs to expand the spectral response range and improve photoelectric performance. A CsPbBr3MW / CdSe NB composite device was fabricated, such as... Figure 20 As shown.

[0079] Electrical characteristics of CsPbBr3MW / CdSe NB devices Figure 21 (a) is a CsPbBr3MW / CdSe NB hybrid optoelectronic device at a bias voltage of 3 V and a wavelength of 530 nm (optical power density of 1.6 mW / cm²). 2 The IV curves of photocurrent under laser irradiation and dark conditions are shown.

[0080] The results show that the dark current is 2.33 × 10⁻⁶. -10 A, photocurrent is 1.17 × 10 -5 A. Calculations show that the on / off ratio of this composite photodetector is 5.02 × 10⁻⁶. 4 It exhibits excellent optical switching characteristics. Compared with the pure CsPbBr3MW device, the CsPbBr3MW / CdSe NB photodetector has improved photocurrent and dark current to a certain extent, especially the photocurrent, which is significantly improved compared with the single device; the photocurrent-to-dark-current ratio is 45.5 times that of the single CsPbBr3MW device.

[0081] This study demonstrates the formation of a hybrid photodetector by combining CsPbBr3MWs with CdSeNB, which fully leverages the excellent properties of both materials in photodetector devices. This is mainly attributed to the transfer of charge carriers from CsPbBr3 to CdSeNB. Therefore, charge carriers can be easily separated and transported to the electrodes, which will greatly improve the photoelectric performance of the device. Figure 21 (b) is the logarithmic IV curve of the CsPbBr3MWs / CdSe NB hybrid optoelectronic device. It can be seen that the dark current curve is a bit rough and not smooth, which may be due to the high sensitivity of the optoelectronic device to incident light, resulting in unstable current when there is no light.

[0082] Photoconductive properties of CsPbBr3MW / CdSe NB devices With the rapid development of society and technology, single materials are no longer sufficient to meet the huge demand for multifunctional detection. Therefore, integrating different semiconductors is a feasible strategy for constructing multifunctional devices.

[0083] Since CdSe NB (with a bandgap of 1.7 eV) is a direct bandgap semiconductor material, and CsPbBr3 is considered an emerging material with good absorption in the 300-550 nm wavelength range, the integrated photodetector of CdSe NB and CsPbBr3 will exhibit a wider response range.

[0084] Figure 22 This is the spectral response diagram of the CsPbBr3MW / CdSeNB device. Clearly, the device exhibits good wavelength selectivity. It can be seen that due to the addition of CdSeNB, the composite device displays a broad spectral response in the approximately 300-740 nm range. Furthermore, compared to a single CsPbBr3 substrate, the response range is broadened, and it exhibits strong photoresponse wavelengths at 530 nm and 710 nm. After 720 nm, the device's sensitivity to illumination decreases sharply. Next, the photoelectric performance of the composite device will be tested at 530 nm and 710 nm.

[0085] Photoelectric properties of CsPbBr3MW / CdSe NB devices Figure 23 (ab) shows the IV characteristics of the detector under different light intensities.

[0086] Under a bias voltage of 3 V, a 530 nm laser was used as the light source to test and analyze the photoelectric performance of the CsPbBr3MWs / CdSe NB hybrid optoelectronic device. It can be seen that the photocurrent gradually increases with increasing light intensity, indicating that the number of photogenerated carriers is proportional to the absorbed photon flux.

[0087] Figure 23 (c) represents the relationship between photocurrent and optical power density. The best fit value of θ is 0.95 under the condition of 530 nm. Figure 23 (d) represents the relationship between R and EQE and optical power density. The calculated R and EQE values ​​for the device under 530 nm wavelength laser irradiation are 1.63 × 10⁻⁶. 3 A / W and 3.82×10 5 %.

[0088] Figure 24 (ab) shows the current-voltage (IV) characteristics of the device under different light intensities.

[0089] Under a bias voltage of 3 V, the performance of a CsPbBr3MW / CdSe NB photodetector was tested and analyzed using a 710 nm laser as the light source. It can be seen that the photocurrent gradually increases with increasing light intensity, indicating that the number of photogenerated carriers is proportional to the absorbed photon flux. Figure 24 (c) Represents the relationship between photocurrent and optical power density, using a power law: The best fit value for θ was 0.95 under the conditions of 3 V and 710 nm.

[0090] Figure 24 (d) shows the relationship between R and EQE and optical power density. According to the formula, the R and EQE values ​​of the device under 710 nm wavelength laser irradiation are 1.06 × 10⁻⁶. 3 A / W and 1.85×10 5 %.

[0091] Figure 25 (ab) show the performance of a CsPbBr3MW / CdSe NB device (3 V bias) under illumination at 530 nm and 710 nm, respectively. Relationship with optical power density.

[0092] The detectors of the device at 530 nm and 710 nm were calculated to be 5.33 × 10⁻⁶. 12 and 3.46×10 12 Jones.

[0093] from Figure 24 (cd) and Figure 25 (ab) shows that as the light intensity increases, the values ​​of R, EOE and D* all decrease significantly, indicating that there is a non-negligible recombination loss in the photodetector.

[0094] IT characteristics of CsPbBr3MW / CdSeNB devices Response speed is one of the most important parameters for describing photodetectors.

[0095] Figure 26 The time-resolved current variation under medium-period illumination clearly demonstrates the repeatable and reversible photosensing behavior of the CsPbBr3MW / CdSeNB device. Figure 26 (a) shows the IT curves measured by continuous switching under 530nm illumination with bias voltages of 1V, 3V, 5V, and 7V. It can be seen that the CsPbBr3MW / CdSeNB device gradually increases with increasing bias voltage and eventually tends to saturate. It can also be seen that it exhibits excellent periodicity and reversible stability in the continuous switching period characteristics. Figure 26 (b) shows the voltage rise and fall edges of the resistor tested using an oscilloscope, with rise and fall edges of 16 and 34 ms, respectively. In summary, it can be demonstrated that the introduction of CdSeNB significantly improves the performance of CsPbBr3-based photodetectors, particularly in terms of high on / off ratio and responsivity.

[0096] When a single CsPbBr3MW is combined with CdSeNB, the photoelectric performance of the composite device is significantly improved.

[0097] Meanwhile, the prepared CsPbBr3MW / CdSeNB composite devices are competitive with most CsPbBr3-based composite devices because they have better photoelectric properties and a wider spectral response range (300-740 nm).

[0098] CdSeNBs were grown by thermal evaporation; the surface morphology and microstructure of CdSeNBs were analyzed by scanning electron microscopy and transmission electron microscopy.

[0099] In this scheme, a CsPbBr3MW / CdSeNB hybrid photodetector is synthesized by transferring a single CdSeNB to a single CsPbBr3MW, thus constructing a parallel hybrid device using the two materials. Secondly, both the composite material and the pure CsPbBr3MW exhibit bandgap absorption at 530 nm, with the composite material showing stronger bandgap absorption than the pure CsPbBr3MW. Furthermore, the composite material also exhibits bandgap absorption around 710 nm, which can be considered as co-absorption. This enhanced light absorption is beneficial for the application of the composite device.

[0100] The CsPbBr3MW / CdSeNB composite device exhibits a large photoresponse in the 300-740 nm range, with two photoresponse peaks at 530 nm and 710 nm. Therefore, the photoelectric performance of the CsPbBr3MW / CdSeNB composite device was studied using 530 nm and 710 nm as representative values.

[0101] The CsPbBr3MW / CdSeNB structure is beneficial for improving the optoelectronic performance of devices because the combination of a fully inorganic perovskite layer with high photon absorption and a carrier transport layer opens up more possibilities for building high-performance detectors. It combines high light absorption and high conductivity, giving full play to the advantages of the large absorption coefficient and high quantum efficiency of fully inorganic perovskites, as well as the excellent performance of two-dimensional materials, and may provide reference and inspiration for future novel high-performance optoelectronic devices.

[0102] In this scheme, CsPbBr3MWs were fabricated using an in-plane self-assembly method. SEM characterization revealed that the obtained CsPbBr3MWs were large in size, uniformly distributed, and had a smooth, flat surface. Subsequently, single CsPbBr3MW devices were fabricated, and their photoelectric performance was tested. The results showed that the CsPbBr3MW-based photodetector exhibited a significant on / off current ratio (1.11 × 10⁻⁶). 3 High detectability (2.9×10⁻⁶) 10 The device exhibits high responsivity (2.7 A / W) and high wavelength selectivity. Secondly, the spectral response in the 300–600 nm range was measured. The results show that the device demonstrates a broad optical response range in the 300–550 nm wavelength range, with a maximum optical response wavelength of 530 nm, exhibiting good wavelength selectivity.

[0103] CdSe NB was grown by CVD and analyzed by SEM, TEM and UV-vis methods to obtain single-crystal nanoribbons with smooth, flat surfaces, few defects and high crystallinity.

[0104] A single CdSe NB was transferred onto a single CsPbBr3MW to fabricate a CsPbBr3MW / CdSe NB hybrid device. CsPbBr3 is a direct bandgap semiconductor with advantages such as low trapped state density, high carrier mobility, and long electron-hole diffusion length. It also possesses excellent optical properties such as tunable emission wavelength and strong light absorption, making it a promising material for optoelectronic devices. Secondly, the two-dimensional semiconductor material CdSe NB, with its high conductivity, serves as a carrier transport layer. Therefore, fabricating a CsPbBr3MW / CdSe NB hybrid device fully leverages the advantages of both materials, not only improving the optoelectronic performance of the hybrid device but also expanding its photoresponse range from 300-550 nm (pure CsPbBr3MW) to 300-740 nm (CsPbBr3MW / CdSe NB). Analysis of the optoelectronic performance of the hybrid device shows that the on / off ratio of the CsPbBr3MW / CdSe NB hybrid optoelectronic device is significantly improved compared to the single material. Its rise and fall edges are 16 and 34 ms, respectively. The CsPbBr3MWs / CdSe NB hybrid device not only extends the photoresponse range but also effectively promotes carrier separation, thus improving photoelectric performance.

[0105] Compared with other all-inorganic perovskite / semiconductor materials, the CsPbBr3MW / CdSeNB device exhibits higher responsivity and photoelectric properties, higher quantum efficiency and on / off ratio, and faster response speed. Furthermore, the device's response range is broadened. The results show that the CsPbBr3MW / CdSeNB structure is beneficial for improving the device's photoelectric performance because the combination of a high-photon-absorption all-inorganic perovskite layer and a carrier transport layer opens up more possibilities for constructing high-performance detectors. This is because it combines high light absorption and high conductivity, fully leveraging the advantages of high absorption coefficient and high quantum efficiency of all-inorganic perovskites, as well as the excellent properties of two-dimensional materials, and providing a strategy for constructing novel high-performance optoelectronic devices in the future.

[0106] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for fabricating a hybrid device based on CsPbBr3MWs and CdSeNB, characterized in that: Includes the following steps, The prepared CsPbBr3 precursor solution was dropped onto a Si / SiO2 substrate that had been treated with a plasma analyzer, covered with a smooth and flat PDMS film, and then dried. After drying, the PDMS film was removed and observed with an optical microscope. Substrates on which CsPbBr3MWs grew well were selected for later use. 50 μL of CdSeNB dispersion was taken with a pipette and dropped onto the selected CsPbBr3MWs substrate. The solution was allowed to evaporate completely. The CsPbBr3MWs and CdSeNB composite samples were observed and selected using an optical microscope; an 80 nm Au electrode was deposited using an evaporation system; the CsPbBr3MWs / CdSeNB hybrid optoelectronic device was successfully fabricated. The preparation method of the CsPbBr3MWs specifically includes the following steps: S1. A smooth and flat PDMS film is fabricated on a Si substrate with a smooth and flat microstructure without photoresist. S2. Weigh out equal molar ratios of PbBr2 and CsBr powder using an electronic balance, dissolve them in a container containing 1 ml of dimethyl sulfoxide (DMSO) solution, and seal tightly. S3. Place the container in an oil bath and stir at 65°C for 6 hours. After cooling to room temperature, filter it using a 0.45μm polytetrafluoroethylene needle filter. S4. Use a pipette to draw 10 μL of CsPbBr3 solution and drop it onto the treated Si / SiO2 substrate. Then cut a PDMS film the size of the silicon wafer and press it on the substrate. Place it on a 45°C hot plate to dry overnight. Step S5: After removing the covering substrate, CsPbBr3MWs material is obtained; The preparation method of the CdSeNB includes the following steps: Si / SiO2 substrates cut into 1.0×2.0cm were ultrasonically cleaned in acetone, ethanol and deionized water for 10min respectively, then dried with nitrogen gas, and then a 10nm thick Au film was sputtered on the substrate. Take an appropriate amount of CdSe powder, pack it into a ceramic boat and compact it to prevent it from being blown away by the gas; place the ceramic boat in the middle of the quartz tube and place the silicon substrate 6 cm downstream of the ceramic boat for the deposition of two-dimensional materials. Place the quartz tube into the tubular furnace, determine its position, and close the flange. Then, purge the tubular furnace with Ar / H2 gas containing 5% H2. After cleaning, a vacuum was drawn, and the flow rate of the mixed gas was controlled at 15 sccm. The temperature was increased from room temperature to 300°C at a rate of 10°C / min, and then held at this temperature for 10 min. Next, the temperature was increased to 820°C and held at this temperature for 120 min. After cooling to room temperature, it was removed, and the growth of CdSeNBs was completed.

2. The CsPbBr3MWs and CdSeNB hybrid devices prepared by the method described in claim 1 are used in semiconductor materials, photodetectors, solar cells, and light-emitting diodes.